2017
DOI: 10.1038/s41598-017-02594-3
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation of dopamine and serotonin function modulates the feedback-related negativity during altruistic punishment

Abstract: Why do humans cooperate and often punish norm violations of others? In the present study, we sought to investigate the genetic bases of altruistic punishment (AP), which refers to the costly punishment of norm violations with potential benefit for other individuals. Recent evidence suggests that norm violations and unfairness are indexed by the feedback-related negativity (FRN), an anterior cingulate cortex (ACC) generated neural response to expectancy violations. Given evidence on the role of serotonin and do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 85 publications
3
10
0
1
Order By: Relevance
“…For the outcome-focused moral judgment, individuals tend to be concerned about the norm of saving more people by sacrificing one person and thus rate impersonal action harm as less norm violation (Greene et al ., 2001). With regard to the roles of 5-HTTLPR in moral behaviors, the S allele of the 5-HTTLPR has been related to the high permissibility for unfair dictator assignments of the Dictator Game (Enge et al ., 2017), which suggests that the S allele could promote permissibility of preserving one’s well-being by sacrificing other’s interests. Here, we found that individuals with the SS genotype are more likely to rate impersonal action harms as permissibility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the outcome-focused moral judgment, individuals tend to be concerned about the norm of saving more people by sacrificing one person and thus rate impersonal action harm as less norm violation (Greene et al ., 2001). With regard to the roles of 5-HTTLPR in moral behaviors, the S allele of the 5-HTTLPR has been related to the high permissibility for unfair dictator assignments of the Dictator Game (Enge et al ., 2017), which suggests that the S allele could promote permissibility of preserving one’s well-being by sacrificing other’s interests. Here, we found that individuals with the SS genotype are more likely to rate impersonal action harms as permissibility.…”
Section: Discussionmentioning
confidence: 99%
“…Here, we found that individuals with the SS genotype are more likely to rate impersonal action harms as permissibility. Thus, given the link of the S allele with high permissibility for dictator assignments (Enge et al ., 2017), the roles of the S allele 5-HTTLPR in increasing permissibility of impersonal harms may be attributed to its effect on decreasing injustice sense of utilitarian outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, there are several genetic testing panels, using SNPs identified in genome-wide association studies, available for certain diseases [13][14][15]. However, only a few studies were performed on symptom outcomes and individual genomics [20][21][22]. Because of the complexity, such as outcome variables, sample size, and different distribution of genotypes in different racial populations, conducting translational behavioral investigation is challenging.…”
Section: Discussionmentioning
confidence: 99%
“…Genotypes included in further analysis were in Hardy-Weinberg-Equilibrium (HWE): DRD4 VNTR: χ 2 = 25.40; df = 15; p = .092; DAT1 VNTR: χ 2 = 1.50, df = 3, p = .45; COMT val158met: χ 2 = 0.71; df = 1, p = .48. HWE calculations were made using the HWxtest package (Engels, 2014) for R core.…”
Section: Genotyping and Cgs Calculationmentioning
confidence: 99%